2016
DOI: 10.1039/c6en00278a
|View full text |Cite
|
Sign up to set email alerts
|

Protein corona-induced modification of silver nanoparticle aggregation in simulated gastric fluid

Abstract: Due to their widespread incorporation into a range of biomedical and consumer products, the ingestion of silver nanoparticles (AgNPs) is of considerable concern to human health. However, the extent to which AgNPs will be modified within the gastric compartment of the gastrointestinal tract is still poorly understood. Studies have yet to fully evaluate the extent of physicochemical changes to AgNPs in the presence of biological macromolecules, such as pepsin, the most abundant protein in the stomach, or the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 81 publications
7
53
0
Order By: Relevance
“…This is in agreement with other studies that also mentioned the clustering of AgNPs submitted to a gastric digestion. [36,41,42,47] AgNPs agglomeration was also detected by UV-vis spectroscopy in line with published results. [36,47,51] Indeed, UV-vis spectroscopy allows to distinguish dissolution from agglomeration of AgNPs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in agreement with other studies that also mentioned the clustering of AgNPs submitted to a gastric digestion. [36,41,42,47] AgNPs agglomeration was also detected by UV-vis spectroscopy in line with published results. [36,47,51] Indeed, UV-vis spectroscopy allows to distinguish dissolution from agglomeration of AgNPs.…”
Section: Discussionsupporting
confidence: 90%
“…However, most studies focusing on the impact of AgNPs on intestinal cells were performed with pristine nanoparticles (NPs), [26][27][28][29][30][31][32][33] i.e., nanoparticles directly purchased from manufacturer or synthesized in the laboratory. [34] These experiments do not consider their interaction with food components and the potential alterations occurring in the gastrointestinal tract, [35][36][37] while it has been shown that AgNPs can be affected by the surrounding conditions. [38] Due to their high reactivity, NMs might interact with food components, such as carbohydrates, lipids, proteins, and minerals, which may influence their size, charge, agglomeration state, and surface composition.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnologists in the field of food sciences have started to acknowledge the importance of PC on the fate and toxicity of ingested food-grade NPs [8]. It has been shown that incubation of silver NPs in simulated gastric media containing pepsin can result in the formation of PC, which facilitates NP aggregation [9,10]. Similarly, PC can also build upon the surface of polystyrene NPs exposed to various digestive enzymes [11].…”
Section: What Is It Known So Far?mentioning
confidence: 99%
“…To simulate the behavior of E171 into the intestinal tract we used two solutions that simulate gastric and intestinal fluids. Briefly, simulated gastric fluid (SGF) contained 80 m m HCl and 34 m m NaCl (Sigma‐Aldrich) in a final volume of 1 L of distilled water and pH 1.1 (Ault et al, ). Simulated intestinal fluid (SIF) contained 60 m m KH 2 PO 4 and 20 m m NaOH in distilled water in a final volume of 1 L with pH 6.8 (Stippler, Sabine, & Jennifer, ).…”
Section: Methodsmentioning
confidence: 99%